The reformatting of state control in Vietnam. (1st October 2008) - Chris Dixon,
Abstract : This paper examines changing forms of state control in Vietnam. It argues that while reform and rapid economic growth have been associated with promotion of market activity and decline in directly controlled activity as measured by the number of SOEs (State Owned Enterprises) and the state sector's share of gross industrial output, this conceals a major reformatting of state control. Direct control over equitised SOEs has been maintained by the state holding the majority of the shares. Meanwhile complex, often inconsistently enforced and interpreted regulation ties enterprises to the state, a situation reinforced by the state's ability to facilitate (or not) access to credit, technology, market information and know-how. Perhaps even more significant is the manner in which, in much of the new economy in Vietnam, the former distinction between the public and the private has been blurred, and in many cases new hybrid forms have emerged that defy conventional classification. This reformatting of power has been accompanied by the emergence of some serious contradictions which may come to undermine the developmental effectiveness of the Vietnamese state.